Emotion and rationality by degree: a history of the hospitality degree program at Niagara College Canada. (1st October 2020) - Clark, Heather; Weaver, Adam
ABSTRACT: Hospitality and tourism degree programs are not typically studied in a historical context. Chronicling the past with respect to the formation and evolution of a post-secondary academic qualification has merit but research of this nature is not often conceptually sophisticated. A historical study of a four-year hospitality degree program is being undertaken at Niagara College Canada, an educational institution that has offered this academic qualification since 2003. The history of the degree program is distinguished by two themes: the degree is both a collective endeavour imbued with emotions and a product of calculated, business-driven deliberations. A degree, in this paper, is portrayed as an emotional enterprise; the work associated with its creation and management is informed by emotions and rational, commercial discourse. This paper uses the hospitality degree at Niagara College Canada as a case study to pursue a deeper understanding of the making and shaping of an academic qualification.